Analisis Instrumen Tes Hasil Belajar Matematika Kelas V Sekolah Dasar - Marselina Alsedis Sidok; Magdalena Dhema; Agnesia Bergita Anomeisa (Jurnal Syntax Admiration, 2023)
This study aims to determine the quality of the Instrument of Mathematics Learning Outcomes Class V Primary Schools used by educators seen from the level of validity, level of reliability, level of truth, and the level of power distinguishing questions. This research was conducted at SDN Moro in the even semester of the academic year 2021/2022. The population of this study was all 96 students. The sampling technique in this study is to use purposive sampling technique. The sample in this study was 21 SDN Moro SDN students. This study uses quantitative methods. Data collection techniques in this study are tests. Data Analysis Researchers use quantitative descriptive analysis with a percentage. Based on the results of the analysis of the level of validity, reliability, difficulty level, and distinguishing power it can be seen that the quality of the test instrument as a whole is good questions and stored in question banks, namely 5 questions or 17%, revised and used 11 questions or 37% and discarded 14 questions or 46%.